Adorno and philosophical modernism : the inside of things - Foster, Roger, 1971- (Lexington Books, 2016)
This book explores contemporary continental philosophy and aesthetics, focusing on the work of philosopher and musicologist Theodor W. Adorno. Roger Foster addresses the problem of post-Kantian reason in relation to the pathologies of experience, alienation, the transformative and ethical import of aesthetic experience, the relation between philosophy and social critique, and language as disclosure rather than correspondence.